Patriots and Pinheads: The Propagandistic Stylings of the Fox News Channels “The O'Reilly Factor’' - Lewandowski, Tadeusz (Stylistyka, 2010)
The American talk show The O ’Reilly Factor premiered in 1996 on media mogul Rupert Murdoch’s Fox News Channel. Hosted by conservative commentator Bill O’Reilly (1949-), the Factor tackles social and political issues with guests from a variety of fields, and is the highest-rated cable news program in the United States, averaging approximately 3.5 million viewers a night. O’Reilly is the most controversial leader of a new wave of ultra-conservative media pundits that have appeared on Fox News over the last decade, who together have forged a new in-your-face reporting style that has garnered top ratings for the entire network. O’Reilly claims to uphold Fox’s motto of ‘Fair and Balanced’ coverage, and has labeled his own show the ‘no spin zone.’ Here he indulges in over-the-top denunciations of the ‘radical’ liberal establishment, promotes an anti-immigrant, anti-minority, anti-welfare and anti-abortion platform, and casts himself as the disgruntled voice of patriotic working-class Americans. Most distinctive is his interviewing style: in doing battle with liberal opponents he frequently resorts to the bellicose phrase ‘Shut up!’ among other invectives. Though such histrionics have earned him great fame, O’Reilly's reporting has come under considerable scrutiny from media watchdog groups such as Media Matters for America and Fairness and Accuracy in Reporting (FAIR), both of which condemn him for extreme bias and inaccuracy. In addition, a 2007 study of The O 'Reilly Factor by the researchers at the Indiana University School of Journalism has concluded that the program regularly employs propaganda techniques defined by the Institute of Propaganda Analysis in the 1930s. This paper analyzes the provocative stylistic content of The O ’Reilly Factor, and examines the various criticisms the program and its host have so combatively drawn.